Kształtowanie się polonijnego systemu antroponimicznego w Stanach Zjednoczonych - Wierzbicka, Elżbieta (Acta Universitatis Lodziensis. Folia Linguistica, 1993)
Americans of Polish origin very often change their Polish first names and surnames into some English equivalents. This process began very long ago, but the peak of it occured in the thirties of the twentieth century. There are both intralingual and extralingual reasons for the process, the former being for example phonological differences between Polish and English, the latter being the easier adaptation of people whose names are English to the society. The research that I made among Polish emigrants and their descendants in the USA has resulted in the material comprising of over 5000 cases of changing of a Polish surname, and 112 typical changes of Polish first names into English. From the linguistic point of view one can distinguish five manners of the Americanization of Polish first names, namely equivalence (eg. Piotr vs Peter), translation (eg. Sławomira vs Gloria), association (eg. Wojciech as Adalbert), sound adaptation (eg. Bożena vs Bonnie), substitution (eg. Bolesław vs George), and three manners of the Americanization of Polish surnames, that is substitution (eg. Czarnecki vs Scott), translation (eg. Grudzień vs December), hybridization (eg. Falkowski vs Faulkner). As a result of all the above changes there has evolved a system that is antroponimie to a different configuration of variants of an allonom than the configuration that is found in the Polish language spoken in Poland. The changes differ with respect to the frequency of their occurence; the phonetic changes are most frequent, whereas the morphological variants are very rare. There has emerged still another type of variants, namely pragmatic variants, eg. Ryszard vs Dick. This new antroponimie system of Americans of Polish origin is a part of their new language in which there are different developmental tendencies from those that are found in the Polish language that is spoken in Poland.